Development of a framework of carbon accounting and management on the township level in China. (15th September 2022) - Dong, Yahong; Zhao, Yating; Zhang, Jun; Liu, Peng
Abstract: The regional management on greenhouse gas (GHG) emissions is essential to the success of global carbon reduction. However, previous studies mostly focused on the city or country levels, while the management of GHG emissions on the township level has not been fully studied. This study proposed a framework of carbon management on the township level and developed a calculation tool for accounting GHG emissions. The case study of Lingshan Island, located in eastern China, was conducted through a site visit and interviews. A questionnaire survey was performed to collect data for carbon accounting. It is found that the island had a negative carbon emission of −1336 t CO2 e in 2020, which is mostly contributed from energy and electricity consumption. Due to the COVID-19 pandemic, the number of tourists decreased in 2020 and the carbon emission was 224 t CO2 e lower than in 2019. The proposed framework consists of five steps and requires the collaboration of the government, the locals, researchers and other stakeholders. The framework was validated through a focus group meeting and the suggestions on carbon management at township level were provided. This study paves a way of carbon accounting and management for the less urbanized regions. Graphical abstract: Image 1 Highlights: Calculation Tool of Regional Carbon Emissions (CToRCE) was developed. A framework of carbon management was proposed on the township level. Lingshan Island was a net negative carbon town with −1333 t CO2 e in 2020. COVID-19 lead to the lower carbon emission of 221 t CO2 e in 2020 than in 2019.